2022
DOI: 10.3390/molecules27103234
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Inhibits Biofilm and Virulence in Listeria monocytogenes as a Quorum-Sensing Inhibitor

Abstract: Listeria monocytogenes is a major foodborne pathogen that can cause listeriosis in humans and animals. Andrographolide is known as a natural antibiotic and exhibits good antibacterial activity. We aimed to investigate the effect of andrographolide on two quorum-sensing (QS) systems, LuxS/AI-2 and Agr/AIP of L. monocytogenes, as well as QS-controlled phenotypes in this study. Our results showed that neither luxS expression nor AI-2 production was affected by andrographolide. Nevertheless, andrographolide signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We used a previously described biofilm CLSM method ( Yu et al., 2022 ). Briefly, biofilms were grown on confocal Petri dishes for 24 h in the absence or presence of DNase I (final concentration, 66.7 U/L).…”
Section: Methodsmentioning
confidence: 99%
“…We used a previously described biofilm CLSM method ( Yu et al., 2022 ). Briefly, biofilms were grown on confocal Petri dishes for 24 h in the absence or presence of DNase I (final concentration, 66.7 U/L).…”
Section: Methodsmentioning
confidence: 99%
“…They found that andrographolide significantly decrease the lactate dehydrogenase release, F-actin cytoskeleton polymerization, and bacterial adhesion to chicken type II pneumocytes by inhibiting the expression of QS signaling molecule AI-2 and virulence factors ( Guo et al, 2014 ). However, study also showed that andrographolide had no effect on the production of AI-2, but significantly decreased the expression level of arg gene and the activity of arg promoter P 2 , leading to inhibition of the biofilm formation and virulence of L. monocytogenes ( Yu et al, 2022 ).…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Specifically, AG can hinder the growth of bacterial biofilms, inhibit the virulence factors, separate the adhesion between bacteria, and destroy the bacterial integrity in direct bacteriostatic action. 24 Nevertheless, the clinical application of AG is still difficult due to its poor solubility. Hence, there is a thorough effort to increase the clinical effectiveness of AG by modifying the structure to increase the solubility or by improving the delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, AG can hinder the growth of bacterial biofilms, inhibit the virulence factors, separate the adhesion between bacteria, and destroy the bacterial integrity in direct bacteriostatic action. 24 …”
Section: Introductionmentioning
confidence: 99%